THE CONTENT OF ORGANIC MATTER IN WATER AND SEDIMENT OF PULAU HALANG MUKA DISCRICT ROKAN HILIR RIAU PROVINCE - Efendi, Musanif; Nedi, Syahril; Siregar, Yusni Ikhwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
Organic matter is one indicator of environmental fertility either on land or at sea. Content Organic matter in the waters will experience an increase caused by discharges from households, agriculture, industry and organic waste from land to coast. The objective of this research is to know the content of organic material in water and sediment in the waters of Coast Mirror and the relation of organic matter content to water and sediment. The result of calculation of organic matter content in water ranged from 26.6 – 49.3 mg/l and the content of organic matter in sediment ranged from 3.9 – 5.1 %. Furthermore, through simple linear regression test known that the relationship of organic matter content in water and sediment has a weak relationship with the correlation r = 0.53. The analysis of sedimentary fractions in the pulau halang muka is dominated by muddy substrates.